2014
DOI: 10.1002/humu.22700
|View full text |Cite
|
Sign up to set email alerts
|

New Target Genes in Endometrial Tumors Show a Role for the Estrogen-Receptor Pathway in Microsatellite-Unstable Cancers

Abstract: Microsatellite instability (MSI) in tumors results in an accumulation of mutations in (target) genes. Previous studies suggest that the profile of target genes differs according to tumor type. This paper describes the first genome-wide search for target genes for mismatch repair-deficient endometrial cancers. Genes expressed in normal endometrium containing coding repeats were analyzed for mutations in tumors. We identified 44 possible genes of which seven are highly mutated (>15%). Some candidates were also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The overall JAK1 mutation frequency of 28% in our large series of MSI endometrial cancers is in line with findings from two recent smaller studies [4, 5]. Both studies also showed that JAK1 frameshift mutations in MSI tumors are tissue specific and significantly less important in colorectal cancers as compared with endometrial cancers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall JAK1 mutation frequency of 28% in our large series of MSI endometrial cancers is in line with findings from two recent smaller studies [4, 5]. Both studies also showed that JAK1 frameshift mutations in MSI tumors are tissue specific and significantly less important in colorectal cancers as compared with endometrial cancers.…”
Section: Discussionsupporting
confidence: 91%
“…colorectal- and ovarian cancer), whereas others, such as JAK1 , have a very restricted occurrence in MSI endometrial cancers [3–6]. MSI endometrial cancers show a remarkably high number of JAK1 frameshift mutations that may have clinical implications [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, specific tumorigenesis pathways associated to a specific type of tissue might have been missed using this strategy. That was the reason why we performed an unbiased screen for target gene mutations in endometrial carcinomas [9] .…”
Section: Reviewmentioning
confidence: 99%
“…Doing so we identified 44 possible target genes of which seven are highly mutated (>15%). Some candidates were also found mutated in colorectal and gastric tumors [9] .…”
Section: Target Genes In Endometrial Carcinomasmentioning
confidence: 99%
See 1 more Smart Citation